Per pass analysis of thrombus composition retrieved by mechanical thrombectomy. Issue 6 (December 2021) - Abbasi, Mehdi; Kvamme, Peter; Layton, Kennith F; Hanel, Ricardo A; Almekhlafi, Mohammed A; Delgado, Josser E; Pereira, Vitor M; Patel, Biraj M; Jahromi, Babak S; Yoo, Albert J; Nogueira, Raul G; Gounis, Matthew J; et al.
Background and aim: Mechanical thrombectomy (MT) for large vessel occlusion often requires multiple passes to retrieve the entire thrombus load. In this multi-institutional study we sought to examine the composition of thrombus fragments retrieved with each pass during MT. Methods: Patients who required multiple passes during thrombectomy were included. Histopathological evaluation of thrombus fragments retrieved from each pass was performed using Martius Scarlet Blue staining and the composition of each thrombus component including RBC, fibrin and platelet was determined using image analysis software. Results: 154 patients underwent MT and 868 passes was performed which resulted in 263 thrombus fragments retrieval. The analysis of thrombus components per pass showed higher RBC, lower fibrin and platelet composition in the pass 1 and 2 when compared to pass 3 and passes 4 or more combined (P values <0.05). There were no significant differences between thrombus fragments retrieved in pass 1 and pass 2 in terms of RBC, WBC, fibrin, and platelet composition (P values >0.05). Similarly, when each composition of thrombus fragments retrieved in pass 3 and passes 4 or more combined were compared with each other, no significant difference was noted (P values >0.05). Conclusion: Our findings confirm that thrombus fragments retrieved with each pass differed significantly in histological content. Fragments in the first passes were associated with lower fibrin and platelet composition compared to fragments retrieved in passes three and four or higher. Also, thrombus fragments retrieved after failed pass were associated with higher fibrin and platelet components.